2020
DOI: 10.33233/rbfe.v19i1.3985
|View full text |Cite
|
Sign up to set email alerts
|

Calistenia e exercício com o peso corporal: conceitos distintos ou sinônimos científicos?

Abstract: Bodyweight exercises (also popularly known as calisthenics) is a classic training method and its practice has been widespread since the 19th century, but little evidenced in the scientific literature over the years. This type of training aims to promote multi-system adaptations using body weight as an overload with no or few implements [1–3]. This characteristic makes exercise with body weight easy to apply, in addition to having an excellent cost-benefit ratio when compared to other training possibilities tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…On the other hand, the bodyweight training (BWT) emerged as an alternative training method that allows the use of exercises without implements to promote health in aging. The characteristics of this method are the realization of physical exercises using body weight as only overload with no or few implements [ 11 ], being a safe option for older women [ 12 , 13 , 14 ]. This training method uses basic movement patterns, such as squat, pull, and push, similarly to the activities of daily living and promoting gains in coordination, an important factor in preventing falls in older people [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the bodyweight training (BWT) emerged as an alternative training method that allows the use of exercises without implements to promote health in aging. The characteristics of this method are the realization of physical exercises using body weight as only overload with no or few implements [ 11 ], being a safe option for older women [ 12 , 13 , 14 ]. This training method uses basic movement patterns, such as squat, pull, and push, similarly to the activities of daily living and promoting gains in coordination, an important factor in preventing falls in older people [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, among the alternatives, bodyweight training (BWT) has been widely used, proving to be a viable option for this population [4]. It is a training that uses little or no implement [5] aiming to improve physical abilities with the use of bodyweight as overload [6]. In fact, applying BWT, Silva and Zácaro [7] found effects on knee flexion strength, and Lord et al [8] found positive results in balance, reaction time, neuromuscular control and risk of falls, demonstrating the effectiveness of this method in variables related to the functionality of the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Já é relatado na literatura que o ECIAI promove ajustes cardiorrespiratórios e metabólicos vigorosos equivalentes aos encontrados em protocolos de SIC (Gist et al, 2014). Os exercícios com o peso corporal (exercícios calistênicos) vêm ocupando lugar de destaque no cenário mundial por ser um exercício de baixo custo e que promove rápidas melhoras no condicionamento físico com o mínimo de tempo gasto para o treinamento diário (Chaves et al, 2020;Gist et al, 2014).…”
Section: Discussionunclassified